EMOTIONAL INTELLIGENCE AND EMPLOYEE PERFORMANCE IN TELECOMMUNICATION INDUSTRY IN IMO STATE, NIGERIA - Maxwell Nwinye; Laguo Livingstone Gilbert (Scholars Digest Publishing, 2025)
This study examined emotional intelligence and employee performance in telecommunication industry in Imo State, Nigeria. This study was guided by two measures of emotional intelligence like self-awareness and social-awareness, including two proxies of employee performance such as adaptive performance and task performance. The researcher employed survey design and random sampling method useful in collection of data. This study comprises population size of 203 employees selected from the three carefully chosen telecommunication companies in Imo State. Managers and senior staff were the employees available for the study. A sample size of 135 employees was realized through the aid of Taro Yamane’s formula. Questionnaire was used as the primary research instrument while information received from company reports and Imo State government statistics served as the secondary source of the study. The research instrument was validated by experts in the field. The reliability of the instrument was determined using Cronbach alpha method. Spearman correlation coefficient was used to test the hypotheses at 0.05 level of significance. The findings of the study indicated that there was a positive significant relationship between self-awareness and adaptive performance as well as social-awareness has significant association with task performance. The researcher affirmed that emotional intelligence is positively connected to employee performance in telecommunication industry in Imo State, Nigeria. The researcher recommended that telecommunication industry should organize a workshop where workers could acquire more skills in emotional intelligence, social awareness, and self -awareness needed in enhancing employee performance.
Keywords: Emotional intelligence, social awareness, self -awareness, employee performance.